AGEN PENYEBAB PENYAKIT AEROMONAD PADA IKAN NILA (Oreochromis niloticus) DAN RESPON IMUN YANG DITIMBULKAN TERHADAP ANTIGEN O DAN H - , drh. Surya Amanu, SU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Freshwater aquaculture in Bali give much harmed by the presence of a deadly disease out break, caused by Aeromonad infection. This research aimed to determine 1) the phenotypic characterization of aeromonad as a basic tool to identify, 2) the genotypic of Aeromonad, 3) Pathological changes of Aeromonad infection, 4) resistance assay against some antibiotics, 5) antigenic properties of bacteria caused an immune response in the Aeromonad, 6) antibody specificity for serologic diagnostic test. Twenty three Tilapia fish samples from Lake Batur, Karangasem and Meliling, Bali with clinical symptoms of skin lesions and exopthalmus, were isolated and identified based on morphological and biochemical properties.. Isolate diinfeksikan pada ikan nila (Oreochromis niloticus) untuk diamati perubahan histopatologi. Both species of Aeromonas was supported by moleculer analysis using sequencing rDNA method. Both Aeromonas was experimentally infected to Tilapia fish to get the histopathological changes. The Aeromonad were tested against the antibiotic sensitivity to ampicilline, erythromycine, doxyxycline, gentamycine and enrofloxacine with Kirby-Bauer method. O and H antigens of Aeromonad were inoculated on rabbit on the weeks of 1, 2, 3 and 4. Antibodies of rabbits were harvested in the week of 5, was measured with tube agglutination and slide agglutination assays. Results of study were analyzed descriptively. The results showed that 21 isolates could be identified as A. hydrophila (11 isolates) and A. salmonicida (10 isolates). Two isolates of A. salmonicida were subspecies achromogenes and 8 isolates subspecies smithia. Both species of Aeromonas were the same as species in Genbank. Aeromonas salmonicida subspecies smithia and achromogenes was closely related. Histopathological changes started to occur on the third day such as congestion of gills, necrosis of kidney, and splenitis. Inflammation would transmitted to kidney, cor, skin, and gut. Aeromonas hydrophila (81,82%) and A. salmonicida (90%) were resistant to ampicilline, however, they were 100% sensitive to enrofloxacine and gentamycine. Antibody titer was 640 against antigen O both of A. hydrophila and A. salmonicida, where as the titer 5120 against antigen H showed by A. hydrophila. There were no cross reaction between antibodies against antigen O and H of A. hydrophila with A. salmonicida isolates. Ccross reaction of the antibody is only found between the O antibodies of both subspecies of A. salmonicida (achromogenes and smithia) with both of these isolates.